Farmers delighted with price information - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Dr M Mukhebi of Kenya Agricultural Commodity Exchange shows the way to a new regional service point in Bungoma, Western Kenya, where farmers can get instant market information, and deal online